Evaluating the Predictors of Persistent Long COVID Symptoms and Their Severity in COVID-19 Survivors 1 Year After Infection - Adam F. Aldhawyan; Mohammed A. BuSaad; Bothayna A. Alamri; Mohammed I. Alsaihati; Bader S. Alanazi; Rawan A. alanazi; Ahmed S. Bahamdan (SAGE Publishing, 2024)
Introduction/objective: As the coronavirus disease 2019 (COVID-19) pandemic progressed, the virus was found to cause long-term health complications known as long COVID (LC). This study aimed to investigate LC symptom severity and the factors associated with the likelihood of persistence beyond 1 year among COVID-19 survivors in Saudi Arabia. Methods: This descriptive, cross-sectional, questionnaire-based study was conducted via convenience sampling between December 1, 2023, and March 1, 2024. In-person interviews were performed, and 845 individuals with persistent symptoms after acute COVID-19 were included. Results: Hair loss and memory impairment were the most reported symptoms. In predicting LC persistence beyond 12 months, women were found to have higher odds of being symptomatic than men, and individuals from moderate-to-high-income households were more likely to report persistent symptoms than those from low-income households. Each additional acute COVID-19 symptom increased the likelihood of persistent symptoms by 1.14 times. Reporting more symptoms in the first 6 months post-infection significantly reduced the odds of long-term symptoms by approximately 30%. Conclusion: LC symptom severity varies among patients, and sociodemographic and clinical factors influence the likelihood of experiencing symptoms beyond 1 year. Understanding these factors can provide insights and help optimize management, leading to improved patient outcomes.